Synthesis and reactivity of a 1,4-dihydropyrazine derivative - Rodrigues, Anabela (2004)
N,N-Bis-(tert-butoxycarbonyl)-2,5-bis-methoxycarbonyl-1,4-dihydropyrazine can be obtained in high yield by treatment of the methyl ester of N-(4-toluenesulfonyl)-N-(tert-butoxycarbonyl)-alpha,beta-didehydroalanine with dimethylaminopyridine and potassium carbonate. This compound was used as substrate in Michael addition reactions with several types of nucleophiles. The electrochemical behaviour of this pyrazine derivative was also studied by cyclic voltammetry and by controlled potential electrolysis.